Do gozo à transcendência : uma história da literatura erótica brasileira - Zucchi, Vanessa (2018)
This thesis aims to elucidate the development of Brasilian erotic literature's polysystem in the decades from 1960 to 1980, besides it discusses the representations of eroticism in this repertoire. The main support of the thesis are the concepts of 1) erotic literature, which is defined as any literary narrative with the eroticism in the center; 2) eroticism, as an inner e subjective experience, according to George Bataille's philosophical approach; 3) the theory of polysystems, by Itamar Even Zohar. The literary corpus was constituted from the intersection of these concepts, in order to create an integrated panorama, internally and externally. In the highlighted period, it is possible to realize the formation of the erotic polysystem, its subsequent consolidation and renovation. In the first moment, the focus is on Cassandra Rios and Adelaide Carraro. Subsequently it is made an analysis of two specific cases that illustrate the movement of the polysystem: the publication of mass Literature by L’Oren Publishing House and the short story contest by Status magazine. Finally, regarding the 1980s, it is studied how the erotic literature reacts to "pornographic hangover", characteristic of the period.